TINDAKAN YURIDIS DALAM PUTUSAN NOMOR 59/G/2021/PTUN.MDN: ANALISIS PENYELESAIAN SENGKETA TATA USAHA NEGARA - Okprianti, Reny; Emilson, Nur Husni; Nariyah, Salsabila; Sauly, Aisyah Febryta; Akbar, Febriansyah; Subari, Ahmad; Frananda, Royen (LPPM STIH Awang Long, 2024)
Legal and non-legal considerations of judges in decision number 59/G/2021/PTUN.Mdn Does Decision Number 59/G/2021/PTUN.Mdn reflect the embodiment of the theory of justice? This study also uses a legal analysis method for normative case numbers, namely the author analyzes the context of the State Administrative Court decision Number 59/G/2021/PTUN.Mdn which is then drawn to existing legal regulations, in this case the Law on State Administrative Courts. The Decree of the Regent of Deli Serdang No. 00174/21212/TAP/03/21 dated March 25, 2021 concerning Honorable Dismissal Not at Own Request and Provision of Pension in the name of Dinawati Tarigan is in accordance with the provisions of Article 53 paragraph (2) letter (a) of Law No. 9 of 2004 concerning the First Amendment to Law No. 5 decisions of the State Administrative Court that were challenged were contrary to regulations In addition to legal considerations based on laws and regulations, judges also consider non-legal aspects in making decisions. The Decree of the Regent of Deli Serdang No. 00174/21212/TAP/03/21 dated March 25, 2021 concerning Honorable Dismissal Not at Own Request and Provision of Pension in the name of Dinawati Tarigan was declared invalid by the State Administrative Court.